THE ROLE OF MODERN SCLEROTHERAPY IN VASCULAR SURGERY - Zokhirov Adkhamjon Rafiqovich; Rakhimov Ulugbek Fakhriddin ogli; Khujanova Shokhruza Shukhrat qizi; Sobirov Shokhjakhon Sobirjonovich; Dovudkhonova Sarvinozkhon Jaxongirkhon qizi; Fakhriddinov Firdavs Faxriddinovich; Omonullakhujaev Saidakromkhon Ubaydullaxonovich (Journals Park Publishing, 2023)
To improve the quality of life of patients with dilated veins, suspected varicose veins and patients with comorbidities who do not have indications for a high level of invasiveness, to study the degree of change in working capacity and provide information about it.
Keywords: high radio frequency, pulse, varicose veins, sclerotherapy, diabetes melliteus, flebectomy, ethoxisclerol.